2014
DOI: 10.1007/s12264-013-1459-z
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical reduction of cerebral blood flow after acetazolamide loading: a hemodynamic and metabolic study with 15O PET

Abstract: Paradoxical reduction of cerebral blood flow (CBF) after administration of the vasodilator acetazolamide is the most severe stage of cerebrovascular reactivity failure and is often associated with an increased oxygen extraction fraction (OEF). In this study, we aimed to reveal the mechanism underlying this phenomenon by focusing on the ratio of CBF to cerebral blood volume (CBV) as a marker of regional cerebral perfusion pressure (CPP). In 37 patients with unilateral internal carotid or middle cerebral arteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…PET data were reconstructed using Fourier rebinning 19 and a filtered back projection algorithm with a 1 min frame duration, 128 Â 128 Â 95 matrix size, and 0.43 Â 0.43 Â 0.80 mm 3 voxel size, which included corrections for random and deadtimes without corrections for scatter and attenuation. Figure 3 shows representative volumes of interest (VOIs) drawn in the whole brain and the heart on summed images of 15 3 , respectively (the shapes and volumes of the heart VOIs were identical for all measurements, and only the location was adjusted for a series of PET scans of each animal taken on a single day).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PET data were reconstructed using Fourier rebinning 19 and a filtered back projection algorithm with a 1 min frame duration, 128 Â 128 Â 95 matrix size, and 0.43 Â 0.43 Â 0.80 mm 3 voxel size, which included corrections for random and deadtimes without corrections for scatter and attenuation. Figure 3 shows representative volumes of interest (VOIs) drawn in the whole brain and the heart on summed images of 15 3 , respectively (the shapes and volumes of the heart VOIs were identical for all measurements, and only the location was adjusted for a series of PET scans of each animal taken on a single day).…”
Section: Discussionmentioning
confidence: 99%
“…Since oxygen is a fundamental energy source for brain activity, use of Positron emission tomography (PET) for in vivo quantitative measurements of parameters related to cerebral oxygen metabolism such as cerebral blood flow (CBF), cerebral blood volume (CBV), oxygen extraction fraction (OEF), and cerebral metabolic rate of oxygen (CMRO 2 ) in the presence of 15 O labeled gases ( 15 O-O 2 , 15 O-CO 2 , and 15 O-CO) is of great importance both in clinical [1][2][3][4] and basic settings. [5][6][7] Given the importance of small animal models such as mice and rats to many research fields, the development of noninvasive measurement methods to assess oxygen metabolism in small animals is needed.…”
Section: Introductionmentioning
confidence: 99%
“…PET images were obtained using a SET-3000 GCT/X scanner (Shimadzu Corp, Kyoto, Japan) with arterial blood sampling 15. For cerebral blood volume (CBV) measurement, a static 4 min scan was started 3 min after 1 min of C 15 O gas inhalation (3.0 GBq/min).…”
Section: Methodsmentioning
confidence: 99%
“…Regional CBF and CMRO 2 can be quantitatively evaluated via 15 O-labeled gas and water PET (Hatazawa et al, 1996; Watabe et al, 2014). Our group recently reported that functional correlations in the DMN can be estimated using quantitative 15 O-PET (Aoe et al, 2018).…”
Section: Evaluation Of Functional Correlations Using 15o-gas Petmentioning
confidence: 99%